Barbed suture versus traditional suture in primary total knee arthroplasty: A systematic review and meta-analysis of randomized controlled studies. Issue 21 (22nd May 2020) - Li, Pengbiao; Zhang, Wenhui; Wang, Yanyan; Li, Jinlong; Yan, Peijing; Guo, Shifang; Liu, Jie; Yang, Kehu; He, Zongru; Qian, Yaowen
Abstract: Background: Barbed suture has been widely used in some surgical fields, and it has achieved good results, but the application in total knee arthroplasty is still controversial. Objective: Literature is collected for statistical analysis so as to provide evidence for the use of barbed suture in Total knee arthroplasty. Methods: We searched PubMed, the Cochrane library and EMBASE database for randomized controlled trials (RCTs) using barbed suture and conventional suture to close incisions after primary total knee arthroplasty, and the retrieval time was from July 2019 to the establishment of the database. Literature was screened according to inclusion and exclusion criteria, quality evaluation and data extraction were conducted for the final included literature, and statistical analysis was conducted using RevMan 5.3 software. Results: A total of six RCTs (826 knees) were included in our meta-analysis. The results showed that the re-negative conversion could shorten the wound closure time (MD –4.41, 95% CI −5.11 to −3.72, P < .00001) and reduce the wound closure total cost (MD –282.61, 95% CI –445.36 to –119.85, P = .0007) and acupuncture injury (RR 0.14, 95% CI 0.03–0.78, P = .02), and did not significantly increasing the incidence of complications (RR 0.80, 95% CI 0.05–0.96, P = .38) or suture breakages (RR 4.58, 95% CI 0.16−128.29, P = .37). There were no significant differences in ROM at postoperative 6 weeks and 3 months (MD −0.74, 95% CI −4.19 to 2.71, P = .67; MD −0.30, 95% CI −2.62 to 2.02, P = .80) and no significant differences in KSS at postoperative 6 weeks (MD –0.22, 95% CI –3.10 to 2.66, P = .88). Conclusions: Our study shows that barbed suture is a fast, low-cost, safe and effective suture method in total knee arthroplasty compared with traditional suture, we also need more literature and longer follow-up to confirm this conclusion.